ABOUT THE HISTORY OF THE RUSSIAN INVADER'S ENTRY TO TERMIZ - Raimov Mamasoat Safar ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article covers the study of the past of Termiz and the historiography of scientific literature about it, which includes a number of aspects that can be a separate topic for each scientific research